Green House Sebagai Wadah Penelitian Tanaman Pada Pusat Penelitian Dan Pengembangan Tanaman Pangan Dan Hortikultura Di Kabupaten Maros - Sarjito, Muhammad Sam Putra Yasashi; Marwati, Marwati; Juddah, Safruddin (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2023)
Beef is one of the main staples in Indonesia. This is evidenced by the demand for beef which continues to increase every year, this is not matched by the supply of beef. The breeders are increasingly having difficulty getting adequate land areas for livestock locations and there is still a lack of knowledge about clean and modern farm rearing processes. Makassar City, which is the capital city of South Sulawesi Province with a population of more than 1.5 million people, along with the increase in population in Makassar City, meat consumption also continues to increase with an average meat consumption reaching 15-20 tons of meat. The farm system, which still relies on traditional methods of raising cattle, cannot meet the demand for beef in Makassar City. The presence of this modern farm will increase the supply of meat in Makassar City by accommodating the number of cattle in Makassar City, of course with a breeding process in order to maintain the existing cattle population. The design of this farm applies the concept of eco-friendly architecture, which focuses on waste management, lighting and natural ventilation as a zero waste effort in the farm area.